PEMBUATAN GENERATOR SINKRON UNTUK PEMBANGKIT LISTRIK TENAGA MIKROHIDRO DARI MAGNET MOTOR BEKAS DI DESA KEMUMU BENGKULU UTARA - Hendra .; Muhammad Syaiful; Anizar Indriani (Universitas Bengkulu, 2017)
Community empowerment in improving the knowledge to make a generator by using the recycle of magnet of the motorcycle is part of a community service-based research throughtraining manufacture of generators. This generator can be used to change of mechanicalenergy into the electrical energy. Where as the mechanical energy is obtained from theturbine screw. This training method contains material about the introduction of thegenerator and proceed with the process of manufacture of generators by using recycle ofmotorcycle magnet coil manner. Generators are made tested with the 3 phase of motors asearly movers to get the magnitude of the voltage output of the generator. After the outputvoltage is obtained then followed by using the turbinesscrew, windmills or otherpropulsion to drive the generators. Magnet motor that is made into a generator consists ofseveral magnetic poles are 6, 8 and 12 poles. Mechanism of the generator is expected tohelp the community in generating electrical energy as a power source of the electricalpower and that does not depend anymore on electricity company such as PLN for lighting,drying, cooling and others. Through this training, the potential flow of a river or irrigation water in the village of Kemumu can be utilized by the villagers to meet the need forelectrical energy. Where electrical energy can be used to increasing the economy valueand daily life of rural communities Kemumu. Of the training conducted, it was found thatthe generator capable of producing an electrical voltage of 106 volts with the rotationdrive of screw turbines is 876 rpm and 12 pole magnet generator. The generator with anoutput voltage of 6 obtained by 78, 4 Volt with one load of 15-watt incandescent light bulb.And using four load of 15-watt incandescent light bulbs obtained 58,8 Volt output voltageby using a magnetic generator 8 poles. From these results can be concluded that thegenerators by using the recycle magnet of motorcycle by the community can generate an electric voltage.Keywords: Generator, PLTMH, Electrical Energy, Magnet Motor, Turbin Screw